Bacterial cellulose-hydroxyapatite composites with osteogenic growth peptide (OGP) or pentapeptide OGP on bone regeneration in critical-size calvarial defect model - Pigossi, Suzane C. [UNESP]; Oliveira, Guilherme J. P. L. [UNESP]; Finoti, Livia S. [UNESP]; Nepomuceno, Rafael [UNESP]; Spolidorio, Luis Carlos [UNESP]; Rossa Júnior, Carlos [UNESP]; Ribeiro, Sidney J. L. [UNESP]; Saska, Sybele; Scarel-Caminaga, Raquel M. [UNESP] (Wiley, 2015)
This study aimed to evaluate the potential of bacterial cellulose-hydroxyapatite (BC-HA) composites associated with osteogenic growth peptide (OGP) or pentapeptide OGP(10–14) in bone regeneration in critical-size calvarial defects in mice. In this study, the BC-HA, BC-HA-OGP, and BC-HA-OGP(10–14) membranes were analyzed at 3, 7, 15, 30, 60, and 90 days. In each period, the specimens were evaluated by micro-computed tomography (µCT), descriptive histology, gene expression of bone biomarkers by qPCR and VEGFR-2 (vascular endothelial growth factor) quantification by ELISA. Three days post-operative, Runx2, Tnfrsf11b and Bglap bone biomarkers were upregulated mainly by BC-HA OGP and BC-HA OGP(10–14) membranes, suggesting an acceleration of the osteoblast differentiation/activity with the use of these biomaterials. At 60 and 90 days, a high percentage of bone formation was observed by µCT for BC-HA and BC-HA OGP(10–14) membranes. High expression of some bone biomarkers, such as Alpl, Spp1, and Tnfrsf11b, was also observed for the same membranes on days 60 and 90. In conclusion, the BC-HA membrane promoted a better bone formation in critical-size mice calvarial defects. Nevertheless, incorporation of the peptides at the concentration of 10−9 mol L−1 did not improve bone regeneration potential in the long-term.
Keywords: Biomaterial; Bacterial cellulose; Bone regeneration; Osteogenic peptide; Gene expression